2017 IEEE Workshop on Information Forensics and Security (WIFS) 2017
DOI: 10.1109/wifs.2017.8267653
|View full text |Cite
|
Sign up to set email alerts
|

It's always April fools' day!: On the difficulty of social network misinformation classification via propagation features

Abstract: Given the huge impact that Online Social Networks (OSN) had in the way people get informed and form their opinion, they became an attractive playground for malicious entities that want to spread misinformation, and leverage their effect. In fact, misinformation easily spreads on OSN and is a huge threat for modern society, possibly influencing also the outcome of elections, or even putting people's life at risk (e.g., spreading "anti-vaccines" misinformation). Therefore, it is of paramount importance for our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
(39 reference statements)
1
14
0
2
Order By: Relevance
“…Intuitively, this is related to the difficulty of maintaining a higher number of ties, and the consequent weakness of the links. Conti et al (2017) provide additional empirical evidence reinforcing the hypothesis of echo chambers.…”
Section: The Impact Of Social Media On News Propagationsupporting
confidence: 66%
“…Intuitively, this is related to the difficulty of maintaining a higher number of ties, and the consequent weakness of the links. Conti et al (2017) provide additional empirical evidence reinforcing the hypothesis of echo chambers.…”
Section: The Impact Of Social Media On News Propagationsupporting
confidence: 66%
“…As to those referred papers on Facebook data-sets based on machine learning analysis, Tacchini et al [67] showed that Facebook post can be highly accurately classified based on the users who "liked" them, obtaining classification accuracy over 99%. Additionally, Conti et al [13] focused on Online Social Network (OSN) structural properties of the information cascade as they are inherently difficult to be manipulated obtaining, on a highly imbalanced dataset and using a total of 28 features over three distinct classifiers (Linear Discriminant(LD), Random Forest (RF), Multi-Layer Perceptron (MLP)) classification F-score never exceeded 0.7.…”
Section: Detection Using Computational Methodsmentioning
confidence: 99%
“…On the text processing stage, it is lemmatized based on the SpaCy implementation and its' available large English dictionary 13 . Stop words, punctuation and spaces removal processes are also applied.…”
Section: What? How?mentioning
confidence: 99%
“…La tarea de identificarlas noticias falsas de forma temprana y automática con sistemas informáticos es crucial para no extender su difusión, sin embargo, algunos trabajos ya demuestran la complejidad que esto supone (Conti, Lain, Lazzeretti, Lovisotto, & Quattrociocchi, 2017;Del Vicario, Quattrociocchi, Scala, & Zollo, 2018). Como todavía los sistemas de detección de noticias falsas no son lo suficientemente sofisticados dado el volumen de las mismas, así como el peligro de las mismas para la sociedad en general (solo justificaría cualquier estudio el hecho de combatir el impacto que tienen estas noticias en la toma de decisión de muchos pacientes con problemas graves de salud que se acogen y automedican con remedios milagrosos de falsas noticias en los medios), es fundamental una formación para la ciudadanía sobre la capacidad de detección y evaluación de noticias falsas en cuanto a la información en general, y científica y tecnológica en particular, que difunden.…”
Section: -Competencia Mediática La Identificación De Noticias Falsunclassified